ANALISIS EMPIRIS PRODUKSI KELAPA SAWIT TERHADAP TINGKAT KESEJAHTERAAN PETANI - Taufiq Hidayatullah (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2023)
Even though smallholder oil palm production and CPO prices tend to increase, the welfare of farmers is not in line with this increase. This study aims to analyze, first, the effect of land area and oil palm productivity on palm oil production. Second, the effect of palm oil production and CPO prices on the welfare of farmers. The data used in this study is secondary data sourced from BPS. While the data analysis method uses multiple regression with the Cobb-Douglas production function. The results showed that first, land area and productivity had a positive effect on palm oil production. Land and productivity are mutually reinforcing, each contributing a 1 percent increase in production. Second, palm oil production and CPO prices have a positive effect on the welfare of farmers. Palm oil production and CPO prices are two things that mutually support the welfare of farmers, respectively contributing to increasing the welfare of farmers by 0.22 percent and 0.34 percent.